Evaluation of Evolocumab (AMG 145), a Fully Human Anti‐PCSK9 IgG2 Monoclonal Antibody, in Subjects With Hepatic Impairment. (26th October 2016) - Gibbs, John P.; Slatter, J. Greg; Egbuna, Ogo; Geller, Michelle; Hamilton, Lisa; Dias, Clapton S.; Xu, Ren Y.; Johnson, Jessica; Wasserman, Scott M.; Emery, Maurice G.
Abstract: Evolocumab binds PCSK9, increasing low‐density lipoprotein cholesterol (LDL‐C) receptors and lowering LDL‐C. Target‐mediated evolocumab elimination is attributable to PCSK9 binding. As circulating PCSK9 and LDL‐C levels are primarily regulated by the liver, we compared evolocumab pharmacokinetics, pharmacodynamics, and safety in individuals with and without hepatic impairment. An open‐label, parallel‐group study evaluated the pharmacokinetics of evolocumab in hepatic‐impaired (Child‐Pugh Class A or B) or healthy adults. Participants were classified as having no, mild, or moderate hepatic impairment (n = 8/group) and received a single 140‐mg evolocumab dose. Assessments of unbound evolocumab and PCSK9 were made predose and postdose. Adverse events were monitored throughout the study. No significant association was observed between baseline PCSK9 and increasing level of hepatic impairment. No difference in extent and time course of PCSK9 or LDL‐C reduction was observed despite an apparent decrease in mean unbound evolocumab exposure with increasing hepatic impairment (Jonckheere‐Terpstra trend test; maximum serum concentration P = .18; area under the curve P = .09). Maximum reductions were observed in moderately impaired subjects vs healthy individuals: mean maximum serum concentration –34%; mean area under the concentration‐time curve (AUC) –47%. On average, unbound PCSK9 serum concentrations fell by >80% at 4 hours after a single evolocumab dose. Mean (95% confidence interval) maximum LDL‐C reductions in the healthy, mild, and moderate groups were –57% (–64% to –48%), –70% (–75% to –63%), and –53% (–61% to –43%), respectively. No safety risks were identified. These results support evolocumab use without dose adjustment in patients with active liver disease and mild or moderate hepatic impairment.